Participation in the "Erasmus+": Perspectives on Attitudes, Motivational Drivers and Barriers to Engagement - Kitiashvili , Anastasia (PROFESSIONAL STUDIES: Theory And Practice, 2024)
This study examines students’ engagement in the "Erasmus+" program in Georgia, their attitudes, motivations, obstacles to participation, and the program’s effects on academic and career progress. Survey research was conducted with 215 students, and four focus groups were held with 50 students. The findings revealed, that participants’ success in the "Erasmus+" program was associated with positive attitudes towards the program, students’ motivations, effective preparation, and strong academic and language skills. A higher success rate was observed among female participants particularly within the age group of 23-29. These groups also expressed a desire to pursue further studies and apply for "Erasmus+". Participating in "Erasmus+" projects enhanced the social and academic skills of students, yet the direct impact on job prospects was uncertain. Non participation primarily stems from barriers named by more than half of the surveyed students, such as a lack of information, inadequate support, and financial limitations. Previous experiences with mobility programs also influenced their preferences, as participants displayed a preference for further studies in EU countries, while non-applicants pursued educational opportunities in Georgia followed by EU countries. Through by eliminating the aforementioned barriers, more young people would engage in the "Erasmus+" program, fostering their enhanced educational, professional, personal, and societal development.